2016
DOI: 10.1128/aac.00714-16
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Molecular Epidemiology and Antibiotic Susceptibility of Clostridium difficile Isolates in Pediatric and Adult Patients

Abstract: fThe rising incidence of Clostridium difficile infections (CDIs) in adults is partly related to the global spread of fluoroquinoloneresistant strains, namely, BI/NAP1/027. Although CDIs are also increasingly diagnosed in children, BI/NAP1/027 is relatively uncommon in children. Little is known about the antibiotic susceptibility of pediatric CDI isolates. C. difficile was cultured from tcdB-positive stools collected from children diagnosed with CDI between December 2012 and December 2013 at an academic childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
(28 reference statements)
1
7
0
1
Order By: Relevance
“…29,30 The differential effects of various broad spectrum antibiotics on rates of CDI may reflect variable effects on gut anaerobes and possibly, a direct inhibitor effect of quinolones against C difficile. 31 We also found a higher risk of developing CDI among HCT recipients who had a history of CDI in the 12 months before the current transplant. The increased risk in recipients with a history of prior CDI may reflect increased C difficile colonization or absence of antibodies to the toxin.…”
Section: Ta B L Esupporting
confidence: 55%
See 1 more Smart Citation
“…29,30 The differential effects of various broad spectrum antibiotics on rates of CDI may reflect variable effects on gut anaerobes and possibly, a direct inhibitor effect of quinolones against C difficile. 31 We also found a higher risk of developing CDI among HCT recipients who had a history of CDI in the 12 months before the current transplant. The increased risk in recipients with a history of prior CDI may reflect increased C difficile colonization or absence of antibodies to the toxin.…”
Section: Ta B L Esupporting
confidence: 55%
“…Recent studies examining the use of levofloxacin prophylaxis in leukemia and HCT patients reported reduced positive C difficile test results when compared to placebo or other prophylactic regimens . The differential effects of various broad spectrum antibiotics on rates of CDI may reflect variable effects on gut anaerobes and possibly, a direct inhibitor effect of quinolones against C difficile …”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic susceptibility data were derived from a previous study [14]. Mean inhibitory concentrations (MIC) of the following antibiotics were measured at the Loyola University Chicago Stritch School of Medicine: metronidazole, vancomycin, rifaximin, fidaxomicin, surotomycin, clindamycin, and moxifloxacin (i.e., high-level fluoroquinolone resistance).…”
Section: Methodsmentioning
confidence: 99%
“…The division between medical specialists versus residents was made to depict differences in professional experience. The division between the paediatrics department versus non-paediatrics departments was made to depict epidemiological, clinical and microbiological differences in infectious diseases and because separate diagnostic and treatment guidelines exist for the two [ 21 25 ].…”
Section: Methodsmentioning
confidence: 99%